PENGARUH RASIO CAMELS DAN BANK SIZE TERHADAP NON PERFORMING LOAN (NPL) (Pada Bank BUMN Di Indonesia) - Dahlia Wati; jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACK             The purpose of this research is to examine the effect of CAMELS and Bank size ratio against Non Performing Loan (NPL) at BUMN (Badan Usaha Milik Negara) Bank in Indonesia. Study on BUMN (Badan Usaha Milik Negara) Bank who publish their financial statements in Indonesia Stock Exchange (IDX) from 2011 to 2016. The population in this research is BUMN Bank in Indonesia and not a sharia business unit. The research is using 4 BUMN Bank as the sample and also using purposive sampling technique method.The analysis is done by using Regression Model and Classical Assumption. Based on the results of the simultaneous analysis of the results that the independent variables or CAMELS and Bank Size ratios both have a very good effect on the dependent variable of Non performing Loan (NPL) at BUMN Bank in Indonesia, the result of this research is supported by research conducted by Barus (2016 ), Putri (2017) and Vireyto (2017). Partially that CAMELS Ratio is CAR, NIM, LDR, IRRR does not have good effect to NPL but only KAP and NPM ratio which have good effect to NPL, while the variable Bank Size is very good effect on the variable NPL. It means that the larger the size of a company the greater the transaction sales, assets owned, and market capitalization. This research is supported by research conducted by Putra (2015), Dewi and Ramatha (2015). Keywords :CAMELS Ratio, Bank Size and Non Performing Loan (NPL).